Sexual History Evidence in Rape Trials: Is the Jury Out? - Herriott, Charlotte (Routledge Frontiers of Criminal Justice, 2023)
This book provides an in-depth examination of current, high-profile debates about the use of sexual history evidence in rape trials and its impact on jurors. In doing so, it presents findings of the first mock jury dataset in England and Wales to explore how jurors interpret, discuss, and rely upon such evidence within their deliberations. Drawing on both qualitative and quantitative insights from the 18 mock jury panels, the book highlights the complex, nuanced and intersectional impact of sexual history evidence within the deliberative ideal. Indeed, findings exemplified routine and ongoing prejudicial framings of sexual history amongst jurors, and frequent endorsement of rape myths that served to mistakenly infer relevance and undermine the perceived credibility of the complainant. The findings discussed within this book are therefore key to addressing the current knowledge gap around the impact of sexual history evidence and are embedded within broader discussions about evidential legitimacy in rape trials. The book draws on good practice observed in other jurisdictions to makes numerous recommendations for change. Aiming to inform academic, policy, and legislative discussions in this area, Sexual History Evidence in Rape Trials will be of great interest to students and scholars of Criminal Law and Criminology, as well as policy makers and legal practitioners